TLR2 Derangements Likely Play a Significant Role in the Inflammatory Response and Thrombosis in Patients with Ph(−) Classical Myeloproliferative Neoplasm - Jen Chin Wang; Guanfang Shi; Chi Chen; Ching Wong; Vladimir Gotlieb; Gardith Joseph; Kiron V Nair; Lakshmi Boyapati; Enayati Ladan; James T. Symanowski; Lishi Sun (Mediators of Inflammation)
We investigated the role of toll-like receptors (TLRs) in inflammatory pathways in Philadelphia chromosome-negative myeloproliferative neoplasms (Ph(−)MPNs). TLR2 expression was increased in ET, PV, and MPN (grouped as (PV + (ET) + MF)), whereas TLR4 was elevated only in MPN. TLR3, 7, and 9 were not elevated. Cultured monocyte-derived dendritic cells and plasma assays in TLR2-elevated patients were found to secrete more cytokines than those from TLR2-normal patients. These facts suggest that TLR2 is the major inflammatory pathways in MPN. We also measured S100A9 and reactive oxygen species (ROS), revealing increased S100A9 in PV, MF, and MPN, while ROS were only increased in MF. These data suggests that MPNs initially involve TLR2, with minor contributions from TLR4, and with S100A9, leading to ROS formation, JAK2 mutation, and progression to MF or leukemia. Furthermore, patients with JAK2 mutations or leukocytosis exhibited higher TLR2 expression. In leukocyte–platelet interactions, cells from MPN patients displayed a stronger response to a TLR2 agonist than TLR4 agonist. A TLR2 inhibitor (but not a TLR4 inhibitor) attenuated this response. Thrombosis incidence was higher in TLR2-elevated patients (29%) than in TLR2-normal patients (19%). These findings suggest that TLR2 likely contributes to thrombosis in MPN.